The Importance of Teaching Folk Crafts to Teachers of Technological Education in the Educational Process - Razzokov Bakhtiyor Khabibullaevich; Nishonov Khosilbek Jakhongir ugli (Zien Journals, 2022)
The historical origin of folk crafts dates back to the childhood of mankind. As humankind grew, so did the craftsmanship of the people. As the struggle for survival grew, so did the need for a better life, and mental labor began to separate from manual labor. This article discusses the importance of teaching folk crafts to future teachers of technological education in the educational process.
Keywords: Education; folk crafts; technological education; teaching